Practical Test of HOTS Oriented e-LKPD Materials of Respiratory System for Class XI of Senior High School - Ramadhana, Fitria; Adnan, Adnan; Azis, Andi Asmawati (Universitas Sultan Ageng Tirtayasa, 2023)
The Electronic Student Worksheet (e-LKPD) is HOTS oriented on respiratory system material to produce an e -LKPD that meets applicable criteria. This type of research is Research and Development (R & D) with the ADDIE development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The stages of implementing the e-LKPD were carried out at SMA Negeri 21 Makassar, with the research subjects being two biology teachers and 29 class XI students. The sample was chosen randomly and is intended to provide an unbiased representation of the general population. The results showed that the percentage of e-LKPD product implementation was 78.41%. Furthermore, the implementation results were used to obtain the e-LKPD practicality test through the teacher's response of 9 6, 66 %, and students 8 3, 1 6%. Therefore, the HOTS-oriented e-LKPD on respiratory system material has convenient criteria.